EVALUASI PELAKSANAAN DANA DESA YANG BERSUMBER DARI APBN DI DESA TITIAN MODANG KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI TAHUN ANGGARAN 2015-2016 - Peldi, Adri; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to evaluate the implementation of Village Funds sourced from APBN in Titian Modang Village Kuantan Tengah District Kuantan Singingi Regency Budget Year 2015-2016. This research uses analytical descriptive method that is collecting, compiling, and interpreting existing data then analyze the data, examine it, describe it and examine clearly from various factors related to condition, situation, and phenomenon investigated. This method can certainly describe the journey of an idea, the thought related to the problems that are limited in this study.This study found that the implementation of Village Funds sourced from APBN in Titian Modang Village Kuantan Central District of Kuantan Singingi Regency Budget Year 2015-2016 shows that all money spent has been accounted physically, although from the administrative side not yet fully perfect. However, efforts to learn, improvement, and improvements from the administration side continue to be done to perfection. The weakness of human resources becomes the main obstacle in the effort to improve administrative accountability of the Village Fund.The conclusion is that the implementation of the Village Fund sourced from APBN in Titian Modang Village Kuantan Central District of Kuantan Singingi Regency Budget Year 2015-2016 is still limited to physical responsibility, while the administrative side is still not fully done perfectly. the competence of village government human resources is the main obstacle, so it still requires assistance from the Village Assistant (PD) Kecamatan to adjust the changes of the rules every year.Keywords: Evaluation, Village Fund.